Past pandemics and COVID-19 - Moon, Walt K. (COVID-19 pandemic (BrightPoint Press), 2021)
Examines the criteria for declaring a pandemic, chronicles various historical pandemics throughout history, and discusses how they compare to the COVID-19 pandemic. Includes color photographs, a glossary, and further resources.